Who is overeducated and why? Probit and dynamic mixed multinomial logit analyses of vertical mismatch in East and West Germany - Christina Boll; Julian Sebastian Leppin; Klaus Schömann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2014)
Overeducation is an often overlooked facet of untapped human resources. But who is overeducated and why? Relying on SOEP data 1984-2011, we use probit models for estimating the likelihood of entering overeducation and dynamic mixed multinomial logit models with random effects addressing state dependence and unobserved heterogeneity. As further robustness checks we use three specifications of the target variable, i.e. realized matches, self-assessment and twofold overeducation. We run separate analyses for men and women, East and West Germans and medium and highly educated persons. We find that overeducation is mainly state dependent. Nonetheless, even in the dynamic context staying employed proves to be risk-decreasing. By contrast, scars of past unemployment show up in a higher mismatch risk. Moreover, an employer change does not serve as a suitable exit strategy, and a dual qualification does not show up as a valid insurance against graduates' job mismatch. Overall, effects largely depend on the operationalization of overeducation. We conclude that to combat overeducation, focusing on continuous employment careers and circumventing unintentional withdrawals from the current job is crucial. Moreover, institutional impediments that restrain job match quality for certain groups (migrants, mothers) have to be tackled. – – Überqualifikation ist ein zuweilen übersehener Aspekt in der Debatte um ungenutzte Fachkräftepotenziale. Aber wer ist überqualifiziert, und warum? Basierend auf Daten des Sozio-oekonomischen Panels (SOEP) der Wellen 1984-2011 schätzen wir mit Probitmodellen die Wahrscheinlichkeit für neue Überqualifikation sowie mit dynamischen Multinomialen Mixed Logit-Modellen mit zufälligen Effekten die Wahrscheinlichkeit für Überqualifikation unter Berücksichtigung von Pfadabhängigkeit und unbeobachteter Populationsheterogenität. Das Messfehlerproblem kontrollieren wir durch drei verschiedene Spezifikationen der abhängigen Variable, die selbsteingeschätzte Überqualifikation, die statistische Überqualifikation (Realized Matches) sowie eine Kombination aus beidem. Wir führen die Schätzungen getrennt für Männer und Frauen, Ost- und Westdeutsche sowie Personen mittlerer und hoher Bildung durch. Unsere Analysen zeigen, dass Überqualifikation ein hohes Beharrungsvermögen hat. Allerdings vermindert Erwerbserfahrung das Risiko der Überqualifikation auch im dynamischen Modell unter Kontrolle unbeobachteter Heterogenität. Narbeneffekte früherer Arbeitslosigkeit hingegen zeigen sich in einem höheren Überqualifikationsrisiko. Weder ein Arbeitgeberwechsel noch (bei Akademiker/innen) eine Doppelqualifikation in Form von Lehre plus Studium taugen als wirksame Ausweichstrategien. Um Überqualifikation im Job zu vermindern, scheinen Strategien, die konti-nuierliche Erwerbskarrieren fördern, vielversprechend zu sein. Für bestimmte Gruppen am Arbeitsmarkt (Migranten, Mütter) erschweren zudem institutionelle Barrieren ein gutes Jobmatch, die es gezielt anzugehen gilt.
Keywords: J24; C25; C33; J71; 330; overeducation; dynamic mixed multinomial logit; probit model; mismatch; Germany; state dependence